Fox Trapping: A Book of Instruction Telling How to Trap, Snare, Poison and Shoot : A Valuable Book for Trappers - Harding, A. R. (Arthur Robert), 1871-1930 (Salt Lake City, UT : Project Gutenberg, 2010)
"Fox Trapping: A Book of Instruction Telling How to Trap, Snare, Poison and$1! =(B" edited by A. R. Harding is a practical manual focusing on the art of fox trapping, likely written in the early 20th century. The book serves as a comprehensive guide for novice and experienced trappers alike, detailing various methods of trapping, snaring, and baiting foxes. Its content is informed by contributions from seasoned trappers across America, making it a valuable resource for those interested in the subject. The opening of the book sets the stage for an extensive exploration of fox trapping techniques. It starts with a brief historical context, suggesting that mastering these methods would take centuries. Harding emphasizes the importance of personal experiences shared by other trappers, detailing the distribution of fox species throughout North America and their cunning nature. He notes the significance of scent and bait, asserting that success depends on understanding fox behavior. The detailed list of chapters foreshadows a structured approach to various trapping techniques, from general information to specific methods tailored to different conditions and regions. Overall, the beginning positions the book as both an instructional resource and a compilation of trappers' collective wisdom. (This is an automatically generated summary.)s
Release date is 2010-10-15
Produced by Linda M. Everhart, Blairstown, Missouri
Keywords: Fox trapping